1983
DOI: 10.1159/000233380
|View full text |Cite
|
Sign up to set email alerts
|

Airway Response to Leukotriene D<sub>4</sub> in Rhesus Monkeys

Abstract: We studied the effect of leukotriene D4 (LTD4) given by aerosol challenge on asthmatic and normal monkeys. The response to LTD4 occurred within 2 min., was prolonged at higher concentrations, was reversed by epinephrine, and more closely resembled an antigen response than a histamine response. Since LTD4 concentrations of 30–100 μg/ml produced a response similar to 2–20 mg/ml of histamine, the LTD4 was 300–900 times as potent as histamine on a molar basis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Dahlen et al [7] detected LTC4, LTD4, and LTE4 after allergen challenge of lung tissue from asthmatics. Inhalation of LTC4 and LTD4 to monkeys and human subjects suggested a contributory role of leukotrienes during asthmatic attack [3,16]. However, there are few re ports about the release in vivo of LTs from asthmatic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Dahlen et al [7] detected LTC4, LTD4, and LTE4 after allergen challenge of lung tissue from asthmatics. Inhalation of LTC4 and LTD4 to monkeys and human subjects suggested a contributory role of leukotrienes during asthmatic attack [3,16]. However, there are few re ports about the release in vivo of LTs from asthmatic patients.…”
Section: Introductionmentioning
confidence: 99%
“…This model has been used for characterization of rhesus bronchial responses to LTD4 [3], PAF [4], and other bioactive mediators.…”
Section: Discussionmentioning
confidence: 99%
“…We now report that SP produces an airway re sponse analogous in quality to that resulting from an tigen, LTD4, PAF or histamine [2][3][4]17], The concen tration of SP producing a response is analogous to the concentration of histamine that produces an airway response in this species [ 17], The concentration of SP producing an airway re sponse was similar in rhesus monkeys with positive skin reactivity to AA antigen whether or not the ani mal had airway reactivity to AA. Previous studies of these populations of monkeys have shown that the animals with IgE antibody against AA, shown by cu taneous reactivity to AA, which also had an airway response to AA, had airway hyperactivity as demon strated by carbachol responsiveness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations